167 The pathogenic implications of prelamin a accumulation in cardiomyocytes: a model of premature cardiac senescence?. (6th June 2015) - Brayson, Daniel; Protti, Andrea; Ehler, Elisabeth; Vizcay, Gema; Warley, Alice; Shah, Ajay M; Shanahan, Catherine
Abstract : Introduction: Mutations in the LMNA gene, which encodes the nuclear intermediate filament proteins lamins A and C, lead to a number of premature ageing syndromes, including Hutchinson Gilford Progeria syndrome (HGPS) and Emery Dreifuss muscular dystrophy (EDMD) as well as dilated cardiomyopathy (DCM). Some causal mutations disrupt lamin A processing, resulting in the accumulation of the lamin A precursor, prelamin A, however it is not clear to what extent accumulated prelamin A contributes to DCM. Here we identify DCM patients with cardiomyocyte accumulation of prelamin A and explore the impact of prelamin A accumulation in vivo . Methods: We generated a novel line of targeted transgenic mice that accumulate prelamin A specifically in cardiomyocytes (PLA Tg mice), by expressing an uncleavable form of prelamin A, driven by Cre expression from the myosin light chain 2 ventricular (MLC2v) promoter. Results: Immunofluorescence staining of human DCM biopsies showed the presence of nuclear prelamin A in cardiomyocytes. PLA Tg mice were born without any obvious phenotype but manifested retarded growth by 3 weeks of age and succumbed to heart failure at ˜5 weeks. At 4 weeks, MRI showed a marked dilatation of the cardiac chambers and a decline in cardiac function in vivo . Ejection fraction (EF) was substantially depressed in PLA Tg micecompared with wildtype indicating DCM and heart failure. Cardiac histology showed marked cardiomyocyte disarray and profound fibrosis. Biochemical and microscopic analyses indicated disruption of the linkers of nucleoskeleton to cytoskeleton complex and perinuclear intermediate filament network and was supported by electron micrographs showing nuclear morphology defects. Myocardial infiltration of CD45 positive cells coincided with the expression of γ-H2AX, phosphorylated ATM and increased NF-κB signalling, which suggested an inflammatory response initiated by DNA damage. This may be related to the senescence associated secretory phenotype (SASP) as senescence associated β-galactosidase was also expressed in PLA Tg myocardium. Conclusion: We have demonstrated prelamin A accumulation in the nuclei of human DCM biopsies and show that overexpression of prelamin A in a transgenic mouse model leads to an early decline in cardiac function and premature myocardial senescence.